2019
DOI: 10.4055/cios.2019.11.4.427
|View full text |Cite
|
Sign up to set email alerts
|

Is Acromial Fracture after Reverse Total Shoulder Arthroplasty a Negligible Complication?: A Systematic Review

Abstract: BackgroundThe purpose of this study was to investigate the incidence of acromial fracture after reverse total shoulder arthroplasty (RTSA) and clinical and radiological outcomes of treatment of the fracture.MethodsA systematic review was performed to identify studies that reported the results of treatment of acromial fractures after RTSA. A literature search was conducted by two investigators using four databases (PubMed, Embase, Cochrane, and Ovid Medline).ResultsFifteen studies (2,857 shoulders) satisfied ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 24 publications
1
36
0
3
Order By: Relevance
“…Because this ligament is routinely detached during a superolateral approach, one would expect a higher incidence of scapular spine fractures after a superolateral than after a deltopectoral approach. The review of Cho et al, however, showed that the opposite is the case [37].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Because this ligament is routinely detached during a superolateral approach, one would expect a higher incidence of scapular spine fractures after a superolateral than after a deltopectoral approach. The review of Cho et al, however, showed that the opposite is the case [37].…”
Section: Discussionmentioning
confidence: 99%
“…This is obviously not the case. Most reported fractures appear within the first year after surgery [22,26,28,37]. Neyton et al [28] described 13 scapular fractures that already occurred at a mean 3.3 months postoperatively and Dubrow et al [22] reported on 14 acromial fractures that occurred at an average of 5.1 months after RSA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, RSA is not a panacea, and it has its own limitations. For example, Cho CH [31] believed that we should pay great attention to the complications of acromion fractures that commonly occur after surgery. Since RSA is limited by glenoid loosening and instability, prosthesis implantation failure may occur, Song IS et al [32] believed that hemiarthroplasty could better solve such problems, and postoperative follow-up score and joint range of motion were satisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral reverse total shoulder arthroplasty (RTSA) is a proven treatment option for in cuff tear arthropathy (CTA), requiring bilateral arthroplasty[ 1 - 3 ]. Acromial and scapular spine fractures after RTSA are a well-known complication that may negatively impact long-term outcomes[ 4 - 6 ]. In patients undergoing bilateral RTSA, bilateral fractures of the acromion or scapular spine are very rare.…”
Section: Introductionmentioning
confidence: 99%